SUNCT syndrome associated with pituitary Rathke's cyst and responsive to indomethacin: a case report - Cavalcante, Francisca Natiele da Silva; Silva-Néto, Raimundo Pereira; Bordini, Carlos Alberto (Headache Medicine, 2025)
IntroductionShort-lasting unilateral neuralgiform headache attacks (SUNCT/SUNA) is a rare group of headaches classified by the International Classification of Headache Disorders (ICHD-3) in its group 3, the trigeminal-autonomic headaches, and, therefore a primary headache. Rathke’s cleft cysts are sellar or suprasellar non-neoplastic cystic lesions arising from remnants of Rathke’s pouch. These cysts are asymptomatic, but when large, they compress adjacent structures and may present with headache, visual disturbance, and pituitary dysfunction. Cases of secondary SUNCT/SUNA have been reported; however, this is the first report of SUNCT/SUNA associated with a Rathke's cleft cyst.Case ReportA 47-year-old, other while healthy male has been experiencing for the last five years a strictly right sided pain in the orbital and in the frontoparietal area. The pain was felt as if a nail was being driven into his cranium slowly for 5-15 seconds, with intense pain persisting in the area for a few more seconds. Pain intensity was described as excruciating (10/10), a frequency of 4-18 a day, duration of 4- 30 seconds, associated to 2-3 eardrops and moderate conjunctival hyperemia ipsilateral to the pain. Attacks never could be attacks triggered by cutaneous stimuli. Physical and neurological examinations were normal. MRI showed a cystic lesion in the anterior pituitary gland consistent with a Rathke's cleft cyst. The pain was refractory to carbamazepine, amitriptyline, topiramate, and methadone, but was responsive to indomethacin.CommentTo the best of our knowledge, this case report appears to be the first on SUNCT: a) associated with Rathke's cleft cyst; and b) responsive to indomethacin.